EXPLORING POST COLONIAL IDENTITY IN MEENA ALEXANDER’S ATMOSPHERIC EMBROIDERY - Banerjee, Priyanka; Singh, Krishna Murari (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Meena Alexander has undoubtedly contributed immensely to Indian English writing. She has created some memorable works of art not only by writing poems but other forms of writing such as memoir, novels, essays and works of criticism. Her works have always concentrated on the themes of identity, isolation and dislocation. She was an Indian born woman but lived outside India for the major parts of her life. This gave an autobiographical touch to her works wherein she tries to depict her feelings of deep despair as a result of the loss of her homeland and her near ones. She has also been called a poet of the post colonial era who has described her post colonial journey very artistically and has created intricate imageries that produces a varied effect on the mind and heart of the readers. She has also tried to uphold the Indian social values when she depicts the subtle meeting of the Eastern and Western culture. This research paper has tried to depict the post-colonial journey of Meena Alexander in her collection of poetry entitled Atmospheric Embroidery.